2013
DOI: 10.1186/2193-1801-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Probing horseradish peroxidase catalyzed degradation of azo dye from tannery wastewater

Abstract: Biocatalysis based effluent treatment has outclassed the presently favored physico-chemical treatments due to nil sludge production and monetary savings. Azo dyes are commonly employed in the leather industry and pose a great threat to the environment. Here, we show the degradation of C. I. Acid blue 113 using horseradish peroxidase (HRP) assisted with H2O2 as a co-substrate. It was observed that 0.08 U HRP can degrade 3 mL of 30 mg/L dye up to 80% within 45 min with the assistance of 14 μL of H2O2 at pH 6.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Acid Blue 113 dye mediated by horseradish peroxidase is higher at low concentration of dye from 20 to 30 mg/l. Beyond which, the degradation of dye is decreasing abruptly as the concentration of dye increases [92]. Terres et al [90] reported that a dye concentration of 2.5×10 −5 mol/l of Indigo Carmine dye was decolorized by 2 mg of horseradish peroxidase.…”
Section: Optimum Concentration Of Dyementioning
confidence: 98%
See 4 more Smart Citations
“…Acid Blue 113 dye mediated by horseradish peroxidase is higher at low concentration of dye from 20 to 30 mg/l. Beyond which, the degradation of dye is decreasing abruptly as the concentration of dye increases [92]. Terres et al [90] reported that a dye concentration of 2.5×10 −5 mol/l of Indigo Carmine dye was decolorized by 2 mg of horseradish peroxidase.…”
Section: Optimum Concentration Of Dyementioning
confidence: 98%
“…Gholami-Borujeni et al [91] evaluated that decolorization of acid blue-25 (AB-25) dye with horseradish peroxidase was maximum at pH 7 and 0.8. Preethi et al [92] explored that the horseradish peroxidase exhibited higher percentage of color removal of C.I. Acid Blue 113 dye at various pH values such as 4, 6.6, and 9.…”
Section: Effect Of Phmentioning
confidence: 99%
See 3 more Smart Citations